The methodology of the EU Commission to evaluate the impact of direct payments - Ulrich Koester; Jens-Peter Loy (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
The legislator of the European Union (EU) has commissioned the European Commission (EC) to evaluate Pillar 1 measures of the Common Agricultural Policy (CAP), particularly direct income payments. The legislator has laid out the policy objectives and has instructed the EC to specify the impact indicators for the evaluation. This policy brief argues that the EC had to accept the task, which could not be solved with the state-of-the-art methodology generally followed by professional economists. However, the objectives have not been clearly defined by the legislator, and the EC has failed to suggest a clear definition of objectives to measure the expected positive changes resulting from the policy intervention. Moreover, the approach of the EC does not solve the identification problem; it failed to compare the situation with and without direct payments. Thus, the EC is unable to justify the need for direct payments based on its diagnosis and to show that the measure is effective and efficient. The EC uses so-called impact indicators in line with the proposal of the legislator. Specific indicators have been selected to relate to specific objectives (e. g., changes in entrepreneurial income are considered to contribute to the change in the objective 'variable production'). This article argues that this relationship has to be challenged. The same conclusion holds for the impact indicator 'factor income'. The impact indicators used by the EC provide no information about the direct impact on the specific objective variables. Moreover, the EC approach only focuses on potential benefits, and competely neglects economic costs. – – Der Gesetzgeber der Europäischen Union (EU) hat die Europäische Kommission mit der Überprüfung der Maßnahmen der ersten Säule der Gemeinsamen Agrarpolitik (GAP) beauftragt, insbesondere der direkten Einkommensstützung. Dazu hat der Gesetzgeber die politischen Ziele dargelegt und die EU-Kommission angewiesen, Wirkungsindikatoren für eine Bewertung festzulegen. Im folgenden Policy Brief wird dargelegt, dass die EUKommission zwar diese Aufgabe übernehmen musste; diese aber nicht auf der Grundlage der üblichen, allgemein von Wirtschaftsexperten angewandten Methoden erfüllt werden konnte. Eine notwendige Voraussetzung wäre eine klare Definition und Quantifizierung des Zielerreichungsgrades gewesen. Der Gesetzgeber hat aber keine eindeutig definierten Ziele vorgegeben und die EU-Kommission hat keine klaren Zielvorgaben zur Messung der erwarteten positiven Veränderungen durch die politischen Interventionen vorgelegt. Darüber hinaus löst der Ansatz der EU-Kommission ein grundlegendes Problem nicht: es wird kein Vergleich zwischen Situationen mit und ohne Direktzahlungen ermöglicht. Somit kann die EU-Kommission die Notwendigkeit von Direktzahlungen nicht auf der Grundlage von Diagnosen nachweisen und die Wirksamkeit und Effizienz der Maßnahmen belegen. Die EU-Kommission verwendet die so genannten Wirkungsindikatoren auf der Grundlage des gesetzlichen Vorschlags. Zur Zuordnung spezieller Ziele wurden bestimmte Indikatoren ausgewählt (es wird z. B. davon ausgegangen, dass veränderte Unternehmensgewinne zur Veränderung des Ziels "rentable Erzeugung" beitragen). Dieser Artikel belegt, dass diese Beziehung hinterfragt werden muss, ebenso wie die Bedeutung des Wirkungsindikators "Faktoreinkommen". Die von der EU-Kommission verwendeten Wirkungsindikatoren liefern keine Informationen zur direkten Auswirkung auf die speziellen Zielvariablen. Ferner konzentriert sich der Ansatz der EU-Kommission nur auf potenzielle Vorteile und vernachlässigt die ökonomischen Kosten völlig.
urn:nbn:de:gbv:3:2-58065
Keywords: 330